Representación del conflicto armado interno y recuperación de la memoria en el cine documental peruano y documentales hechos en Perú por extranjeros - Ventocilla Maestre, José (2023)
The research aimed to compare foreign and Peruvian documentaries on the Internal Armed Conflict (1980-2000), with the focus of audiovisual representation, in a comparative analytical investigation. The research is of an exploratory level, of narrative design and Grounded Theory, on a sample made up of the documentaries Sibila by Teresa Arredondo (Chile 2012) and Tempestad en los Andes by Mikael Wiström (Sweden, 2014); in front of the Peruvian Walkers of Memory by Heeder Soto (2014) and Volver a Ver by Judith Vélez (2018). With qualitative analysis instruments, the result was that the unsatisfactory and very personal documentary Sibila is followed by the very professional and objective but distant Tempestad en los Andes; while Peruvian documentaries deal with the topic of memory, its recovery and the need to mourn. Walkers of memory is the Andean regional vision, and Volver a ver is a attempt to link past and present. It is concluded that the documentary is a representation device of the past, for the recovery of memory and pending justice.